The price - McLean, Iain.; Johnes, Martin (Cardiff : Welsh Academic Press, 2000)
"The events at Aberfan on the morning of 21 October 1966, when 116 children and 28 adults died in a sea of slurry following the collapse of a coal tip, will forever be etched in the memories of the people of the industrial valleys of South Wales." "In addition to explaining how the disaster happened and why nobody was held responsible, Aberfan: Government & Disasters explains how all the organisations that should have protected the public interest, and specifically the interests of the people of Aberfan, failed to do so."--BOOK JACKET.
The Last Day Before Half-Term -- On Moles and the Habits of Birds: The Unpolitics of Aberfan -- Uneasy Relationships: The Aberfan Disaster, Merthyr Tydfil County Borough Council and Local Politics -- Aberfan and Other Disasters -- The Management of Trauma -- Regulating Gifts of Generosity: Disaster Funds -- The Price of Life: Bereavement Damages -- Holding Corporations to Account -- Government and Disaster.
Includes bibliographical references (p. [242]-266) and index.
Keywords: Spoil bank failures -- Wales